Sistem Informasi Geografis Pemilihan Komoditas Unggulan Pertanian Berdasarkan Zona Agroekologi Di Kabupaten Batang - Samas, Muchmad Achsin Samas (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2024)
Today the use of computers and software every related field of life well widespread social, economic, cultural and even in agriculture. Batang is one area in Central Java province that has the potential of land resources and agriculture are large enough so that needs serious attention. In this case the regional development strategy set by the Local Government Batang focused on economic empowerment of the people by utilizing the competitive advantage of natural resources optimally.GIS or often called a Geographic Information System is a system that uses a computer device, to store, process, retrieve and manipulate geographic data. ZAE or agroecological zone is a grouping of a region based on the physical state of the environment that is almost the same where the diversity of plants can be expected not to be different from the real. With the Geographic Information System based Agricultural Products Top ZAE (agroecological zone) is expected to help the user to know the circumstances surrounding the geographical nature of this case is the entire community Batang county of Central Java and related institutions "Department of Agriculture and Livestock" Batang City Government.Designing GIS based Agricultural Products Top ZAE (Zone Agroecology) Batang county was created using the software makes viewing maps ArcView3.3 in Microsoft Visual Basic 6.0 using Later in the design .exe file it and also use MySQL to build a database of this information system.